A holistic model of education quality in marketing management: an exploratory testing in Spanish universities - Rivera-Camino, Jaime (2010)
Over the last decades, education quality (EQ) assurance has emerged as an important public policy issue. Unfortunately, there is still no agreement on the following issues: EQ definitions, essential assessment indicators, and the fundamental suitability of the models proposed. To fill this vacuum, we propose an EQ model that empirically identifies the resource-capability variables linked to learning outcomes of students, and their association with the competitive positioning of universities.